Processos de educar e educar-se em instituição de atendimento a crianças e adolescentes em situação de risco - Silva, Lígia Maria Portela da (2007)
This work investigated how educators and students, who participated in the program of attending on children and adolescents at risk situation, are educated in order to recognize and respect the differences and also recognize their potentialities and limits, exercising their reflexive, critical, and propositive capacity. It was developed in 2006 and 2007, with the Programa Conquista Criança, a municipal action of attending on children and adolescents at risk situation, in Vitória da Conquista, in the State of Bahia, and it had as field of empiric research two workshops developed by the Program. The goals of the research were: a) to identify and analyze the conceptions of educators and students about education, educator, child and adolescent, and about the aims and the action of the Programa Conquista Criança; b) to analyze the educator s and the student s praxis and their formative process, identifying the different spaces, experiences and moments in which this process takes place. In this work, we understand education as a dialogical process, in the freirian perspective, in which the subjects involved are educated in relation to themselves and to the world, through reflexion and action, noticing reality as a process in continuous transformation. In this way, people educate and are educated in the several social practices in which they are inserted, so education also happens beyond the school space. For the development of the research the following proceedings were used: conversations, non-systematic observations and systematic ones, which were all registered in a field diary; interviews, and after the interview transcriptions, discussion with the participants were made; data analysis elaborated by the researcher was also discussed with the participants. Nineteen sections of observation and ten interviews were accomplished. Two educators and two students participated in this process. The elements that appeared from the adopted procedures permitted us establish the following categories of analysis, systematizing the participants conceptions and experiences: Visions of oneself and of the other; Visions of education and of the educative work in the Programa Conquista Criança; The daily work. That analysis led to the following dimensions understanding which aims at the citizenship formation: To do things together; To question, to listen, to say, to dialogue; To seek coherence of one s own behavior, keeping in touch with one s own history and inner truth; To exercise faith in the human being; To have and provide space of being and acting, exercising autonomy and responsibility. This work contributes to the reflection and elaboration of formative proposals to educators that act in the infantile and juvenile area, offering elements to think about the educative work, specially the one that is developed in institutions of attendance on children and young people at risk situation. The pointed dimensions can be of special interest to think over the practices developed at the school spaces, including the university and processes of education building knowledge.